Impacts of an ageing society on macroeconomics and income inequality: The case of Germany since the 1980s - Jürgen Faik (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
The discussion paper is concerned with the interplay between demography and macroeconomics on one hand and macroeconomics and income inequality on the other hand. For this purpose, several estimation equations are derived by econometric methods (on the empirical basis of the 1984-2010 German Socio-Economic Panel (SOEP) waves). In concrete terms, the macroeconomic variables inflation, economic growth, and unemployment are at first connected with the German demographic ageing; afterwards, these connections are used to produce a nexus between German income inequality and the stated macroeconomic variables (additionally to the exogenous effects of ageing). For the empirical periods examined (1983-2009), there have been a) a (slightly) negative influence of demographic ageing on the inflation rate, b) a (weak) positive effect of ageing on the level - not on the increases (reductions) - of economic growth rates, and c) a somewhat stronger positive impact of demographic ageing on unemployment rates. While the measured income inequality is upwards directly (exogenously) driven by demographic ageing, the mechanisms through the different macroeconomic channels are more difficile: Inflation is positively and unemployment negatively correlated with income inequality, and regarding economic growth a (slightly) concave effect upon income inequality has been observed. All these findings imply that demographic ageing, ceteris paribus and by tendency, diminishes income inequality via inflation and unemployment rate, which is also valid for economic growth (within the empirically relevant value range for the German demographic ageing). But on balance, there is an overcompensating direct, exogenous impact of demographic ageing on inequality in the model used in this paper, and this causes tendencies towards a remarkable increase of German income inequality until 2060. These tendencies are more pronounced in the forecast variant in which a strongly ageing population is assumed.
Keywords: D30; D31; D60; 330; Demographic Ageing; Macroeconomics; Personal Income Distribution; Inequality